Perancangan SIM-Klinik Bagian Pendaftaran Di Klinik X Kabupaten Malang - Maulana, Mohammad; Khalifatulloh, Bhre Diansyah Dinda (Politeknik Negeri Jember, 2025)
The Clinic Management Information System is not yet available at X Clinic, and with 5.000 patient visits in the past three months, the absence of this system has resulted in lengthy service processes. A preliminary study found that many patients visiting X Clinic do not bring their Patient Identity Book (KIB), which further delays the service process. Additionally, medical record duplication frequently occurs in the clinic. This study aimed to design a Clinic Management Information System (SIM-Klinik) using the waterfall model, a systematic and sequential software development approach. The study employed the Research and Development (R&D) method, which is a systematic approach used to create new products or enhance the quality of existing ones. The findings indicated that X Clinic required an information system capable of efficiently and accurately managing patient registration data. The SIM-Klinik design process begins with user needs analysis, followed by the development of DFD Level 0, DFD Level 1, and an ERD model. It is expected that X Clinic will utilize the research findings as a consideration for developing and implementing the SIM-Klinik, ensuring that the infrastructure and facilities align with the system's needs.